Radiation or Chemotherapy rather than Observation may be a Better Modality after Subtotal Resection for Pilocytic Astrocytoma in Children - Jung, Se Yong; Jin, Song Lee; Hahn, Seung Min; Kim, Hyo Sun; Kim, Dong Seok; Seo, Chang-ok; Lyu, Chuhl Joo; Han, Jung Woo (Clinical pediatric hematology-oncology, 2014)
Background: Pilocytic astrocytoma (PA) is a low-grade glioma that occurs primarily in children and young adults. The optimal postoperative treatment modality after subtotal resection (STR) of PAs remains to be elucidated. The aim of this study was to compare the efficacies of different post-STR treatment modalities and to examine the risk factors for the progression of PAs. Methods: We reviewed the medical records of 91 pediatric PA patients in a single institute during a 30-year period. Kaplan-Meier analysis was used to assess overall survival (OS) and progression-free survival (PFS), and Cox proportional hazard models were used to calculate hazard ratios. Results: The median age of 91 patients was 8.9 years (range, 0.3-17.9). GTR was perfomed, whenever possible. Patients who underwent STR afterwards received either radiotherapy, chemotherapy, or were observed without further treatment, according to clinician preference. In total group, 10-year OS was 97.4% and 10-year PFS was 57.2%. In GTR group (N=33), 10-year OS and PFS was 100%. In STR group (N=49), 10-year OS was 97.7%, while 10-year PFS was 38.6%. STR group underwent following postoperative (PO) modalities; observation (PO-Obs, N=32), radiotherapy (PO-RT, N=10), chemotherapy (PO-CTx, N=7). The 10-year PFS rate was higher in patients who received postoperative treatment (either PO-RT or PO-CTx) than in patients who received PO-Obs (62.5% vs 27.0%, P=0.039). In multivariate analysis for STR group, PO-CTx (Hazard ratio (HR)=0.20, P=0.035) and PO-RTx (HR=0.13, P=0.008) were superior to observation, respectively. Conclusion: Radiation and chemotherapy are better post-STR treatment modalities than observation for pediatric PA patients. KCI Citation Count: 0